AN ANALYSIS ON BCG GROWTH SHARING MATRIX - Kader, Md. Abdul; Hossain, Hanif (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
In the 21st century, sustainable improvement of business faces various challenges for the global economic competition. But, these challenges can be overcome by the efficient business strategies. The Boston Consulting Group (BCG) helps the business organizations to develop their efficiency for the successful operation of their business activities. To develop the efficiency of marketing decision making, the BCG Matrix plays an effective tool for strategic planning of product performance in industry and company level. It analyses to identify which strategic business units to invest in, which to sell off, and which to shut down. It helps a company to distribute their available resources through the efficient business management. It is one of the most popular and helpful consulting firms. The paper tries to provide a guideline to the business organizations to choose the best business policies by the use of BCG matrix. Keywords: BCG Matrix, Business Organizations, Business Improvement